SIMULATION MODEL OF THERMAL WATER DISCHARGE EFFLUENT FROM THE STEAM ELECTRICAL GENERATING POWER PLANT “TAMBAK LOROK” AT TANJUNG EMAS HARBOR POND SEMARANG - Sunarsih . (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Simulation model is built for simulating the residual chiller which has now become hot water discarded through an outlet to Tanjung Emas harbor pond. The discarded water is called “thermal effluent” and will cause changes in sea temperature in surrounding areas. The figuring of the casual relationship among those factors is carried out by developing a subsystem model and building it from the model’s subsystems to make a big system. It shows the complexity of the water effluent model. To know the immensity of the effect of each factor and relationship with the simulation of the model. One chooses an approach in the analytical method of dynamic system which uses the program “Powersim version 2.01” copyright 1993 – 1995 ModellData U.S.A. The result of model simulation showed that the temperature effect on the physical-chemical characteristics will improve the water condition with diversity index and will decrease according to the temperature condition with respect to time.